Analysis of the Treatment of Income Tax Article 25 Overpayment at PT AWD - Ayu Arthami Wulandari; I D M Partika; A A Putri Suardani (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
The outbreak of the COVID-19 pandemic in Indonesia has greatly impacted various sectors, including PT AWD which is engaged in SPA services. PT AWD experienced a significant decrease in turnover, causing an overpayment of taxes caused by the payment of tax installments that have been paid every month. Based on this phenomenon, this study was conducted to determine the impact that occurs on PT AWD if it makes restitution or tax burden in managing the tax overpayment. This study was processed using descriptive qualitative techniques with primary data, namely the results of interviews with the employees of PT AWD, and secondary data in the form of company financial statements. Based on this research, it is known that if PT AWD makes restitution, PT AWD will get back the cash that has been paid on condition that it is able to meet the requirements for implementing restitution and comply with its tax obligations. Meanwhile, if PT AWD makes an imposition, the overpayment tax cannot be taken back by the company. Because the overpayment tax has been recognized as an expense in the company's financial statements, so this treatment is more advisable for taxpayers who have a relatively low nominal tax overpayment.